An Analysis of Students’ Reversible Thinking Mathematical Ability on the Material of Flat Sided Space Geometry - Anisa, Syafira Yunita; Sepriyanti, Nana; Khaidir, Christina (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
The ability of reversible mathematical thinking is important for students to support students in the process of learning, thinking and solving various reversible mathematical problems. This ability is needed to minimise the possibility of errors in solving mathematical problems. However, the fact is that students are still unable to master the ability of reversible thinking mathematically, so that students are unable to solve the given mathematical problems. The low ability of students' mathematical reversible thinking is the background in this study. The purpose of this study was to analyse the mathematical reversible thinking ability of students on the material of flat-sided space geometry class VIII at SMPN 8 Bukittinggi. This type of research is a descriptive method that uses a quantitative approach. The subject retrieval technique uses purposive sampling technique. The subjects in this study were 29 students of class VIII.3 at SMPN 8 Bukittinggi. The research instruments used were written tests and interviews. The data analysis technique used by researchers is descriptive statistical data analysis technique. The results of this study indicate that the ability of reversible thinking mathematical class VIII.3 students at SMPN 8 Bukittinggi is categorised as moderate. Based on the results of the study, it is concluded that most students have not been able to master the ability of reversible thinking in flat-sided space geometry material.